CARBON GAS CALCULATION AS A RESULT OF LANDUSE CHANGE BY USING MULTI TEMPORAL LANDSAT TM 7 IMAGES OF 1992-2007 IN LIMA PULUH KOTA REGENCY - Ernawati Ernawati; Yurni Suasanti; Yudi Antomi (Faculty of Geography, Universitas Gadjah Mada, 2010)
The objective of this research is to map landcover change, and releasedcarbon emission in Lima Puluh Kota Regency and Payakumbuh Municipality since1992 – 2007 by using rapid assessment approach based on Multi TemporalLandsat TM 7 Images (1997-2007) of the Remote Sensing Technology. The findingspresent nine landcover classifications identified in Lima Puluh Kota Regency andPayakumbuh Municipality. The current largest landcover change areas arePrimary Forest, and Secondary Forest. Land cover change in Lima Puluh KotaRegency and Payakumbuh Municipality during the period of 1992 – 2007 indicateseven distribution of biomass content in both areas. In total, land cover changesince 1992 - 2007 in Lima Puluh Kota Regency and Payakumbuh Municipalitycontributes to the release of 1,141,458,592 tons of carbon or 76,097,239 tons ofcarbon per year, with 4,185,348,171 tons of CO2 emissions. The data suggest thatduring that period, both areas contributed 279,023,209 tons of CO2 as greenhousegas affecting the Earth’s temperature which then led to global warming.